The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/1755-1315/614/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the error of a magnetic modulation non-contact wide-range device for non-destructive control of high amperage currents

Abstract: The paper provides information on use of direct current (DC) energy in the electric power supply industry of agriculture and water management, hydraulic engineering construction, metallurgy, irrigation and melioration. The need for non-contact non-destructive control of high amperage DCs of high-capacity electrical installations in irrigation and melioration, hydraulic engineering has been identified. The basic requirements for non-contact transducers and sensors of high amperage DC measurements without circui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…From the family of magnetization curves shown in Figure 2, it can be seen that the shape of the curves shown in Figure 2 for all values is similar to the curves shown in (magnetic circuit magnetization [21]. The analysis of these experimental curves showed that if the magnetic material of the samples is isotropic, and the samples have the same geometric dimensions, the same values of the signals both at direct and alternating current, taking into account the influence of the windings (especially in a magnetic circuit with longitudinal modulation), then the same magnetization curves of the magnetic circuit are obtained for both longitudinal and transverse modulation.…”
Section: Analysis Of the Resultssupporting
confidence: 54%
“…From the family of magnetization curves shown in Figure 2, it can be seen that the shape of the curves shown in Figure 2 for all values is similar to the curves shown in (magnetic circuit magnetization [21]. The analysis of these experimental curves showed that if the magnetic material of the samples is isotropic, and the samples have the same geometric dimensions, the same values of the signals both at direct and alternating current, taking into account the influence of the windings (especially in a magnetic circuit with longitudinal modulation), then the same magnetization curves of the magnetic circuit are obtained for both longitudinal and transverse modulation.…”
Section: Analysis Of the Resultssupporting
confidence: 54%
“…Currently, to identify the asymmetry of three-phase currents, CMC are used, having various designs based on various physical effects (on the magneto modulation effect, Hall effect, transformer effect, etc.) [5][6][7][8][9][10].…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 partially shows one of the variants of the developed CWC with basic dimensions. This design was developed based on CC [32] and is a CWC with transversely and longitudinally distributed magnetic parameters. It is characterized by increased sensitivity and an extended range of converted currents.…”
Section: Methodsmentioning
confidence: 99%